Tehnologija kontrolju tehniko-taktichnoi podgotovlenosti futbolistiv visokoi kvalifikacii - Lisenchuk, H.; Tyshchenko, V. (Science in Olympic Sport, 2020)
Objective. Improvement of technology for control of technico-tactical fitness of footballers by substantiating a complex of special indices, as well as quantitative and qualitative criteria of skills of players. Methods. Analysis of scientific and methodological literature and the Internet, analysis of competitive activities of athletes at World championships and Olympics, pedagogical observations, methods of mathematical statistics. Results. The complex of the most significant technico-tactical actions of footballers directly influencing the performance has been substantiated. Quantitative criteria have been developed to characterize their volume and effectiveness during the match, as well as quantitative and qualitative criteria for players` skills. It is possible to get a wide variety of technico-tactical actions of players in quantitative terms, grouping the latter according to the principle of goal orientation, technique of execution, interaction with the opponent, etc. There is rather large variation in virtually all the parameters of technico-tactical actions registered in players of teams of different qualifications - club teams and national teams. Systematization of a large amount of factual material enabled to classify quantitative and qualitative indices of footballers` technico-tactical actions. The qualitative characteristics of individual technico-tactical actions in the form of efficiency coefficients are also given. Among these indices is the percentage of error-free or effectively performed technico-tactical actions of the players in relation to their total number in the game. Conclusion. The findings allow to control technico-tactical fitness of highly skilled footballers on the basis of a set of objective quantitative characteristics.